Antioxidant and antiviral activity of common polyphenols against influenza A virus - Van Cuong, Tran; Nguyen Thi, Thoa (Tay Nguyen Journal of Sciences, 2022)
Herein, we compared the antioxidant activity, cytotoxicity, and antiviral activity of ten common phenolic acids and flavonoids which were naturally occurred in many plants and by-products sources. Antioxidant activity was analyzed using 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2′-azinobis (3 ethylbenzothiazoline-6-sulfonic acids) (ABTS) radical-scavenging activity, while cytotoxicity and antiviral effects of the polyphenols were evaluated using MDCK cells line model. The results showed that different phenolic acids and flavonoids showed a significant difference in antioxidant activities as well as cytotoxicity. Amongst compounds tested, pyrogallol and catechin showed higher DPPH radical scavenging ability, while ellagic acid and quercetin were the higher ability for ABTS assay. Furthermore, our results indicated that the antiviral activity potential varied significantly among polyphenols, that several compounds including gallic acid, quercetin, rutin and vanillic acid were a remarkable inhibited viral infection.